Alteration in perceived health status of those aged 55 to 65 between 2010 and 2017 in France: role of socioeconomic determinants - Laure Carcaillon-Bentata; Noémie Soullier; Nathalie Beltzer; Joël Coste (BMC, 2021)
Abstract Background While life expectancy increases, it is necessary to evaluate whether the additional years are lived in good health, particularly in order to adapt the health care provision and social measures available to support these individuals. Since the 1990s, improvements in perceived health and capacities have been observed among older people, however the changes appear to be far less favourable among the working-age population and, in particular, the generation of people approaching retirement age. The aim of this study was to examine the change in the perceived health status of those aged 55 to 65 in France and investigate the role of socioeconomic factors in this change. Methods Self-reported health (SRH), chronic condition and activity limitation were assessed in 2010 and in 2017 in the French Health Barometer, a general population phone survey conducted on over 25,000 persons living in the community. The prevalence of all three indicators in 2017, and their evolution between 2010 and 2017 were studied according to the main socioeconomic determinants. Results Between 2010 and 2017, there was a sharp increase in the proportion of individuals aged 55-65 reporting poor SRH, chronic condition or activity limitation. A much more marked deterioration was observed in the three indicators among those aged 55-65 than in older age groups, as well as different changes according to socioeconomic determinants. The category of workers with an average level of education was particularly affected by the deterioration. Conclusions This study confirms that the generation approaching retirement age presents a more significant deterioration in health status than those of previous generations. The question of how these trends will be reflected in terms of the burden of dependency at later ages remains open and should encourage increased monitoring of and prevention among this population in future years.